Pattern and perception of wellbeing, quality of work life and quality of care of health professionals in Southwest Nigeria - Oluwagbohunmi A. Awosoga; Nse A. Odunaiya; Olufemi O. Oyewole; Michael O. Ogunlana; Chidozie E. Mbada; Ogochukwu K. Onyeso; Opeyemi M. Adegoke; Ayomikun F. Ayodeji; Adesola C. Odole (BMC, 2022)
Abstract Background Personal wellbeing (PW) including quality of life and work life is a very complex concept that influences health professionals' commitment and productivity. Improving PW may result in positive outcomes and good quality of care. Therefore, this study aimed to assess the pattern and perception of wellbeing, quality of work life (QoWL) and quality of care (QoC) of health professionals (HPs) in southwest Nigeria.  Methods The study was a convergent parallel mixed method design comprising a cross-sectional survey (1580 conveniently selected participants) and a focus group interview (40 purposively selected participants). Participants' PW, quality of life (QoL), QoWL, and QoC were assessed using the PW Index Scale, 5-item World Health Organization Well-Being Index, QoWL questionnaire, and Clinician QoC scale, respectively. The pattern of wellbeing, QoWL and quality of care of HPs were evaluated using t-test and ANOVA tests. Binary regression analysis was used to assess factors that could classify participants as having good or poor wellbeing, QoWL, and quality of care of HPs. The qualitative findings were thematically analyzed following two independent transcriptions. An inductive approach to naming themes was used. Codes were assigned to the data and common codes were grouped into categories, leading to themes and subthemes. Results Of 1600 administered questionnaires, 1580 were returned, giving a 98.75% response rate. Only 45.3%, 43.9%, 39.8% and 38.4% of HP reported good PW, QoL, QoC and QoWL, respectively; while 54.7%, 56.1%, 60.2% and 61.6% were poor. There were significant gender differences in PW and QoC in favor of females. With an increase in age and years of practice, there was a significant increase in PW, QoWL and QoC. As the work volume increased, there was significant decrease in QoWL. Participants with master's or Ph.D. degrees reported improved QoWL while those with diploma reported better QoC. PWI and QoC were significantly different along the type of appointment, with those who held part-time appointments having the least values. The regression models showed that participant's characteristics such as age, gender, designation, and work volume significantly classified health professionals who had good or poor QoC, QoWL, PW and QoL. The focus group interview revealed four themes and 16 sub-themes. The four themes were the definitions of QoC, QoWL, and PW, and dimensions of QoC. Conclusion More than half of health professionals reported poor quality of work life, quality of life and personal wellbeing which were influenced by personal and work-related factors. All these may have influenced the poor quality of care reported, despite the finding of a good knowledge of what quality of care entails.